Study of Pulmonary Function Tests in Rheumatoid Arthritis Patients and to Establish Correlation between Pulmonary Function and Disease Activity of Rheumatoid Arthritis in Eastern India: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
Background: Pulmonary involvement is one of the most common extra-articular manifestation of rheumatoid arthritis (RA) and the second common cause of death due to infection. Pulmonary function tests are widely used to provide objective measure of lung function for detecting and quantifying pulmonary impairments. Material & Methods: This study was hospital based cross sectional nonintervention study. About 100 patients of rheumatoid arthritis have been selected from Rheumatology Clinic (OPD) of R. G. Kar Medical College and Hospital according to the ACR/EULAR diagnostic criteria, 2010. All patients were undergone for Hb% estimation, ESR determination, estimation of serum RA-factor, C-reactive protein and ACPA. Disease Activity of RA had determined by DAS-28 calculator. All cases and controls are undergone lung function test by means of electronic spirometer in the Department of Physiology of the same institute. Results: In our study 82% cases were female and 18% cases were males. In our study we got significant changes in lung function of the RA patients. FVC, FEV1, PEFR and FEF 25-75% etc. were significantly deteriorated, (p-value
Keywords: Rheumatoid arthritis (RA), DAS-28 disease activity score, pulmonary function test (PFT), rheumatoid factor, C-reactive protein, Anti-citrullinated protein antibody (ACPA)